İş Hukukunda iş sağlığı ve güvenliğinin örgütlenmesi - Demir, Ender (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Özel Hukuk Anabilim Dalı / Özel Hukuk Bilim Dalı, 2016)
Bu tezde iş sağlığı ve güvenliği örgütlenmesi ele alınmıştır. Bu kapsamda resmi ve işyeri örgütlenmeleri incelenmiştir. Resmi örgütlenme kamu kurumlarından oluşur. İşyeri örgütlenmesi iş güvenliği uzmanı, işyeri hekimi, diğer sağlık personeli ve iş sağlığı ve güvenliği kurulu ve biriminden oluşmaktadır. 6331 sayılı İş Sağlığı ve Güvenliği Kanunu'na göre işverenler iş sağlığı ve güvenliği önlemlerini almakla yükümlüdür. Bu kapsamda işverenler iş sağlığı ve güvenliği örgütü oluşturmakla yükümlüdür.
Organization of occupational health and safety in Labor Law
Occupational health and safety organization in this thesis are discussed. In this context, official and workplace organization have been examined. Official organizations are public institutions. Occupational safety and health workplace organization consist of occupational physician, occupational safety specialist, technician, occupational nurse, worker's representative and occupational health and safety committee and unit. According to the Occupational Health and Safety Act No. 6331, the employer shall have a duty to ensure the safety and health of workers in every aspect related to the work. In this context, employers are obliged to create occupational health and safety organization.
Keywords: Sağlık örgütlenmesi; Health organizations; Türk İş Hukuku; Turkish Labor Law; Örgütlenme; Organization; İş Hukuku; Labour Law; İş güvenliği; Work safety; İş sağlığı; Occupational health